2022
DOI: 10.1101/2022.10.24.513495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heavy metal pollution characteristics of soil around a copper-nickel mine tailings pond in the northwest arid area of China and evaluation of desert phytoremediation potential

Abstract: Phytoextraction and phytostabilization are two mechanisms used by plants to remove and stabilize heavy metals in soil. However, there has been little research on the extraction/stabilization of heavy metals by desert plants in arid areas. This study analyzed eight heavy metals (Cr, Ni, Cu, Zn, Cd, Pb, Mn, and As) in 10 desert plants and their growth matrices. In addition, the single factor pollution index and Nemerow comprehensive pollution index were used to evaluate soil pollution. Based on the biological ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…However, these results are not related to the high content of Pb in the crops in the study area. Approximately 90% of the Pb content in plants comes from the atmosphere rather than being absorbed from the soil by the roots (Shi et al 2013). Nevertheless, the soil Pb in the study area should be considered potentially harmful under reducing conditions.…”
Section: Nemerow Multifactor Index Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these results are not related to the high content of Pb in the crops in the study area. Approximately 90% of the Pb content in plants comes from the atmosphere rather than being absorbed from the soil by the roots (Shi et al 2013). Nevertheless, the soil Pb in the study area should be considered potentially harmful under reducing conditions.…”
Section: Nemerow Multifactor Index Methodsmentioning
confidence: 99%
“…Indeed, they are not easily absorbed by plants and are relatively safe for the environment. However, when they encounter acids, microorganisms, or chelating agents, residual heavy metals can re-enter the environment and threaten the ecosystem (Shi et al 2013).…”
Section: Analysis Of the Presence And Bioavailability Of Heavy Metals...mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrokinetic Remediation, involving low direct current or potential gradient applied to electrodes, can be integrated with various technologies (Reddy, 2013). Phytoremediation, microbial bioremediation, and biosurfactants are nature-based techniques that offer promising solutions for addressing heavy metal pollution with minimal secondary pollution (Ren et al, 2018;Oyedeji et al, 2022;Shi et al, 2022). Subsurface bioremediation has been recognized as an effective method for remediating shallow aquifers and ensuring safe groundwater.…”
Section: Recommendations For Actionmentioning
confidence: 99%
“…Rhamnolipids, a type of biosurfactant, have demonstrated significant potential in soil remediation due to their ability to enhance the removal of heavy metals and organic contaminants from contaminated soils. Studies have shown that rhamnolipids can effectively stabilize and transport metal nanoparticles in porous media, indicating their potential for use in remediation strategies (Rahman et al, 2022;Shi et al, 2022;Lu et al, 2023). Rhizoremediation, a plantmicrobe symbiosis-based approach, has shown promise in the remediation of mixed-waste contaminated soil.…”
Section: Recommendations For Actionmentioning
confidence: 99%